Penerapan Model Project Based Learning Pada Mata Pelajaran Sejarah Untuk Meningkatkan Hasil Belajar Peserta Didik - Tia Oktarina, Yusnidar, L. R. Retno Susanti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2024)
This research is entitled "Application of the Project Based Learning Model in the History Subject to Improve Learning Outcome". This research is motivated by the low result of students studying history in class X.5 due to the learning model that was not yet interactive. Based on this background, the researcher formulated the research problem how to improve the learning outcome of Class X.5 students in history subject with the material for the arrival of Islam into Indonesia through the Project based Learning (PjBL) learning model. This study aimed to improve student learning outcome by using the classroom action research method (CAR) and the Kemmis and Taggart's research design consisting of planning, implementing, observing, and reflecting. Kemmis and Taggart's research design consists of 2 cycles. The result of this study indicated that the learning outcome of students in class X.5 Class X.5 from 22 Senior High School Students Palembang experienced an improvement during 2 class action cycles. In the pre cycle classical completeness stage that class X.5 achieved was 34%, in the first cycle stage the classical completeness achieved by class X.5 was 65%, and in the second cycle stage the classical completeness achieved by class X.5 was 86%.